2018
DOI: 10.1007/s00345-017-2170-x
|View full text |Cite
|
Sign up to set email alerts
|

Worth a second look: outcomes of patients with initial finding of regular renal tissue in CT-guided renal tumor biopsies

Abstract: An unsuspicious histology in CT-guided renal tumor biopsy does not preclude patients with suspicious renal masses from being diagnosed with malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…For example, as a gold standard for ccRCC diagnosis, renal biopsy has a high sensitivity of diagnosis with a low complication rate of <5% [12];however, due to the asymptomatic of ccRCC at an early stage, it cannot be diagnosed at the early days through renal biopsy. What's more, Sadat-Khonsari et al [13] found that patients with suspicious renal masses cannot be precluded from being diagnosed with malignancies; although, with an unsuspicious histology in CTguided renal tumor biopsy and almost 30% of these patients, further diagnostic or therapeutic workup demonstrated a cancer diagnosis. Previous several studies in other cancer types already showed that survivin can also be measured in the serum using a human surviving enzyme-linked immunosorbent assay [14][15][16][17][18], which makes it a noninvasive method for detecting ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, as a gold standard for ccRCC diagnosis, renal biopsy has a high sensitivity of diagnosis with a low complication rate of <5% [12];however, due to the asymptomatic of ccRCC at an early stage, it cannot be diagnosed at the early days through renal biopsy. What's more, Sadat-Khonsari et al [13] found that patients with suspicious renal masses cannot be precluded from being diagnosed with malignancies; although, with an unsuspicious histology in CTguided renal tumor biopsy and almost 30% of these patients, further diagnostic or therapeutic workup demonstrated a cancer diagnosis. Previous several studies in other cancer types already showed that survivin can also be measured in the serum using a human surviving enzyme-linked immunosorbent assay [14][15][16][17][18], which makes it a noninvasive method for detecting ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Obstruction of the renal pedicle, an inevitable method in NSS, greatly reduces intraoperative blood loss and obtains a clear surgical vision. However, the kidney is in an ischemic state after obstruction, and if the blocking time cannot be controlled, it will lead to postoperative renal damage ( 12 ). Currently, laparoscopic surgery has been applied in clinical practice, but LPN requires strict operation skills of the surgeons such as removing tumors, repairing renal pelvis and renal calyx, renal hemostasis, suture techniques in a narrow space under a laparoscope ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, second-look interpretations and primary readings have been performed in different environments with different clinical priorities and different levels of expertise. Furthermore, in certain radiological environments, there is an emphasis on the quantity of work produced, which is easier to measure than the quality of interpretation [11]. Another limitation is that the scenario where expert MSK radiologists are present to reevaluate the CTs of MM patients is difficult to propose.…”
Section: Discussionmentioning
confidence: 99%
“…In many centres, consultation and second-opinion interpretation of medical images by subspecialty radiologists are routinely performed [8][9][10][11][12]. Therefore, the purpose of this study is to evaluate the increased detection of focal lesions and other radiological findings of subspecialty second-opinion (SSO) consultations for CT examinations in MM patients undergoing stem cell transplantation on standard computed tomography.…”
Section: Introductionmentioning
confidence: 99%